Analysis of Teacher's Efforts to Grow Students' Independent Learning Science Materials Source of Energy during Online Learning in Elementary Schools: Analisis Upaya Guru Menumbuhkan Kemandirian Belajar Siswa Materi IPA Sumber Energi Pada Pembelajaran Daring di Sekolah Dasar - Friska Amelia Putri; Enik Setiyawati (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to describe Teacher's Efforts to Grow Students' Independent Learning Science Materials Source of Energy during Online Learning in Elementary Schools. The research method uses descriptive qualitative. Data collection techniques were taken through observation, interviews and documentation. The subjects in this study were the teacher and 3 4th grade students of SDN Ketegan 1. The results of the study indicate that there are Teacher's Efforts to Grow Students' Independent Learning Science Materials Source of Energy during Online Learning in Elementary Schools namely through: Planning, in the preparation of RPP and syllabus incorporating elements of independence into the RPP. Implementation, Teacher's Efforts to Grow Students' Independent Learning Science Materials Source of Energy during Online Learning in Elementary Schoolsseen in the initial, core and closing activities. In the initial activity, the teacher reminds students to carry out their duties and responsibilities independently. The core activity, the teacher familiarizes students independently with the use of the media used is video appearances and Power Point. Closing activity, the teacher reminds students of independent learning.Evaluation is carried out continuously and is carried out with 3 domains, namely cognitive, affective and psychomotor.